EXPLORING THE IMPACT OF COMPANY SIZE AS A MODERATING VARIABLE ON STOCK PRICE DETERMINANTS - Anlinia, Neiska; Mardi; Handarini, Dwi (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2024)
The research aims to analyze company size in relation to factors influencing stock prices. A fundamental analysis technique is utilized in the evaluation of share prices. Using a purposive sampling approach, the research determines the sample by analyzing the 2022 financial reports of Property and Real Estate. Moderated Regression Analysis (MRA) with Eviews software used to examine the impact of moderating. The results indicate that profitability and liquidity have a significant positive effect on stock prices, while capital structure has a significant negative effect. However, company size is unable to moderate the effects of profitability, liquidity, and capital structure on stock prices. After the Covid-19 pandemic, investors do not simultaneously consider financial performance and company size simultaneously in deciding to invest. This is due to the previous year's decline in Property and Real Estate sales, resulting in decreased company profits. This profit decrease may reduce company revenue, and pandemic conditions have led to increased company expenditures. When making an investment, this study might offer helpful information to take into account.